Neural network disturbance in the medial prefrontal cortex might contribute to cognitive impairments induced by neuroinflammation - Ji, Mu-huo; Lei, Lei; Gao, Da-peng; Tong, Jian-hua; Wang, Yong; Yang, Jian-jun (Brain, behavior, and immunity, 2020)
•Neuroinflammation plays a key role in many neurodegenerative diseases.•LPS decreased intensities of vesicular GABA transporter and PV buttons.•LPS induced abnormal mPFC neural activities and cognitive impairments.•Down-regulation of neuroinflammation improved cognitive performance.•Boosting gamma oscillations by RO-10-5824 improved cognitive performance. Neuroinflammation plays a key role in the progression of many neurodegenerative diseases, yet the underlying mechanism remains largely unexplored. Using an animal model of neuroinflammation induced by repeated lipopolysaccharide (LPS) injections, we found selectively reduced expression of parvalbumin (PV) but not somatostatin (SST) in the medial prefrontal cortex (mPFC). The reduced PV expression resulted in decreased intensities of vesicular GABA transporter and PV buttons, suggesting disinhibition in the mPFC. These further induced abnormal mPFC neural activities and consequently contributed to cognitive impairments. In addition, gamma oscillations supported by PV interneuron function were positively associated with time spent with the novel object in the novel object recognition test. Notably, down-regulation of neuroinflammation by microglia inhibitor minocycline or boosting gamma oscillations by dopamine 4 receptor agonist RO-10-5824 improved cognitive performance. In conclusion, our study proposes neural network disturbance as a likely mechanistic linker between neuroinflammation and cognitive impairments in neurodegeneration and possibly other psychiatric disorders.